2006
DOI: 10.1007/s10815-006-9042-4
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial preparation for in vitro oocyte maturation: Early use of estrogen increases endometrial tissue and requires lower daily dosage: A cross over trial in ‘mock’ cycles

Abstract: Purpose: Determine if estrogen used since the beginning of the menstrual flow could improve endometrial tissue compared to standard endometrial preparation for in vitro maturation cycles.Methods: Twenty polycystic ovary syndrome women were submitted to two estrogen therapy schedules: standard schedule; estrogen began on the day of planned egg retrieval (dosage was based on endometrial thickness); and long schedule; estrogen began on the first day of menstruation. No oocyte retrieval or embryo transfer was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…On this day, endometrial thickness was assessed, and when it was <8 mm the E 2 valerate dosage was increased to 10 mg/day; if it was >8 mm the dose of 6 mg/day was maintained. This endometrial preparation schedule is performed in our service because it has been shown to increase endometrial thickness and to prevent most women from using the higher estrogen dose of 10 mg/day (10). After ET, the luteal phase was supplemented with 30 mg/day of dydrogesterone (Duphaston; Solvay Pharmaceuticals, Pymble, New South Wales, Australia).…”
Section: Endometrial Preparationmentioning
confidence: 99%
“…On this day, endometrial thickness was assessed, and when it was <8 mm the E 2 valerate dosage was increased to 10 mg/day; if it was >8 mm the dose of 6 mg/day was maintained. This endometrial preparation schedule is performed in our service because it has been shown to increase endometrial thickness and to prevent most women from using the higher estrogen dose of 10 mg/day (10). After ET, the luteal phase was supplemented with 30 mg/day of dydrogesterone (Duphaston; Solvay Pharmaceuticals, Pymble, New South Wales, Australia).…”
Section: Endometrial Preparationmentioning
confidence: 99%